The Visual Integrity Approach in Historical City Development: A Comparative Study between Istanbul, Vienna, Kyoto and Yogyakarta - Budiman, Hanif; Mode Jutta; Golda Yuli, Nensi (Journal of Architectural Research and Design Studies, 2023)
Architecture and city landscape study becomes interesting if it is associated with factors that accompany the process of growth and development of the city. The city of Yogyakarta has a unique landscape, derived from the authentic history of the region's landscape configuration, and unique geographical elements, and supported by socio-cultural life based on historical traditions. The pressures and challenges of this condition cannot be avoided with the development of the area, the increasing density, and the emergence of new urban spaces which have physical and visual aspects. This study aims to know the strategy for strengthening visual integrity through the natural and cultural landscape of Yogyakarta as a historic city. The study was discussed by analyzing the basic aspects of visual integration in the form of sequence, orientation, continuity, and complexity. Comparison method between 3 historical cities Vienna, Kyoto, and Istanbul, considered to have the same natural, physical and cultural components. The discussion focuses on descriptive analysis to get the best practices for Yogyakarta city planning. The results of this study show the importance of maintaining the visual integrity of the landscape of the Historical Yogyakarta City area in the face of the pressures of urban development and maintaining the sustainability of the authenticity of city basic values. Keywords: architecture and landscape; authenticity; natural; physical and cultural components